Indicador de fragilidade operacional para priorização e substituição de baterias de chumbo ácido ventilada em subestação - Pereira, Éderson Possobom (2021)
This dissertation presents a methodology for the classification and indication of replacement of ventilated lead acid batteries used in substations through the use of the operational fragility indicator composed of two criteria: equipment situation and operational situation. This indicator allows the recognition of which battery has replacement priority in a set of substations. The equipment situation criterion has the formation of the discharge capacity, conductance, operating time and terminal voltage drop. While the operational situation criterion represents the substation's characteristic as transformed power, existence of battery and backup diesel generator. The criteria that were chosen for decision making are divided into two groups: Equipment Situation Criterion (ESC) and Operational Situation Criterion (OSC). The ESC presents the electrical characteristics of the battery bank while the OSC presents the condition of the equipment with respect to location and backup equipment. The multicriterial analysis methods AHP and PROMETHEE were used in this work. The first to define the weights of the criteria, and the second to obtain the OFI. The operational fragility indicator has an important application in the corrective maintenance planning of the electric utility. The methodology is proven in a case study covering 25 battery banks installed in 18 substations of a Brazilian energy transmitter.